Vitrification of in vitro- and in vivo-produced bovine embryos for direct transfer - Kruse, Shantille, author; Seidel, George E., Jr., advisor; Ahola, Jason K., committee member; Bruemmer, Jason E., committee member (Colorado State University. Libraries, 2012)
The overall objective of my thesis research was to improve procedures for vitrifying bovine blastocysts so as to enable direct embryo transfer to the uterus. Blastocysts were produced using standard in vitro procedures in Experiments 1, 2, and 3. Procedures were done at room temperature, 22 ± 2 °C. Unless otherwise mentioned, all media were made in SynGro®. In Experiment 1, base media contained either 1) normal concentrations of sodium (120 mM) and calcium (2 mM);(CON) or 2) 60 mM sodium + 60 mM choline chloride and 0.5 mM calcium (LOW). Blastocysts were exposed to 5 M ethylene glycol (V1) for 3 min and moved to 6.5 M ethylene glycol + 0.5 M galactose + 18% Ficoll (V2). Straws (0.25 mL) were loaded with a column of 120 μl 1 M galactose followed by an air bubble, then V2 containing embryos followed by an air bubble, and 60 μl 1 M galactose followed by sealing with a plastic plug. After 35 s, embryos were vitrified by either 1) standard cooling in liquid nitrogen cooled air (AIR) for 1 min or 2) cooling via contact of straw walls with columns drilled into an aluminum block immersed in liquid nitrogen (BLK) for 2 min and then directly plunged into liquid nitrogen. These combinations resulted in 4 treatments (AIR x CON; n = 61, AIR x LOW; n = 58, BLK x CON; n = 73, BLK x LOW; n = 54). BLK Embryos were warmed by holding straws in air for 10 s, placing them in a water bath at 37 °C for 20 s, mixing embryos with galactose diluent in the straw for 2 min and expelling. Embryos were recovered, rinsed through holding medium, and cultured in chemically defined medium (similar to synthetic oviduct fluid (SOF)) for 24 h before being evaluated for survival. Post warming survival did not differ (P > 0.10) between treatments (AIR x CON = 42.0%; AIR x LOW = 26.8%; BLK x CON = 21.8%, BLK x LOW = 24.5%). Despite lack of statistical significance, we recommend use of LOW base media because both sodium and calcium levels are reduced. Use of this media should therefore have less chance of sodium and calcium toxicity, and could deter apoptosis. The BLK vitrification method is both easier to use and more consistent. In Experiment 2, we sought to identify the most efficacious cryopreservation method for in vitro-produced bovine blastocysts that would enable direct embryo transfer from 0.25 mL straws used as containers for cryopreservation. Although not a method for direct transfer, Cryotops were chosen to serve as positive controls (CON), as they are the industry standard for vitrification of human embryos. Embryos were cryopreserved by vitrification with a Cryotop (CON; n = 118), using an aluminum block (BLK; n = 128), or by slow freezing (SLF; n = 131). Vitrification procedures were as described above for BLK with the exception that CON embryos were placed in < 1 μl V2 onto Cryotops, and after 35 s, vitrified by plunging directly into liquid nitrogen. Embryos cryopreserved via SLF were exposed to 1.36 M glycerol in modified Dulbecco's PBS + 0.4% BSA (PBS) for 10 min, loaded into 0.25 mL straws, and placed into a freezing machine. Straws were cooled to -6 °C at 4 °C per min, held at -6 °C for 5 min, seeded, held at -6 °C for an additional 10 min, and then cooled to -30 °C at 0.5 °C per min and plunged into liquid nitrogen. After storage for at least 24 h in liquid nitrogen, embryos were warmed/thawed. Embryos cryopreserved via CON were removed from Cryotops by direct placement into a 200 μl drop of 1 M galactose for 2 min, whereas BLK/SLF embryos were warmed/thawed as described above with the exception that glycerol was removed in three 6 min steps from SLF embryos: 0.8 M glycerol + 0.3 M sucrose; 0.4 M glycerol + 0.3 M sucrose; and 0.3 M sucrose followed by PBS for 2 min. After recovery, embryos were rinsed through holding medium and cultured as described above. Post warming survival was greater (P < 0.01) for CON than BLK (85.9% and 70.6%, respectively); BLK was greater (P < 0.01) than SLF (56.1%). Although BLK resulted in lower post-warming survival than CON, it may be an acceptable method for direct transfer, which yielded greater post-warming survival than SLF, the current method used for cryopreservation of bovine embryos. In Experiments 3 and 4, the objective was to compare pregnancy rates of recipients of in vitro-(Exp 3) or in vivo-produced bovine blastocysts (Exp 4) cryopreserved via VIT versus SLF. In vitro-produced embryos were produced by standard procedures. In vivo-produced embryos were recovered 7 d post estrus from crossbred, nonlactating superovulated beef cows. Embryos were cryopreserved via BLK vitrification (VIT; Exp 3, n = 78; Exp 4, n = 46 ) or slow freezing (SLF; Exp 3, n = 78; Exp 4, n = 44). Embryos were cryopreserved and warmed/thawed as described above followed by nonsurgical transfer into non-pregnant cows culled for unknown reasons, but with normal-appearing reproductive tracts. Recipients were d 7 ± 0.5 of the estrous cycle, and each received 2 embryos into the uterine horn ipsilateral to the corpus luteum. Pregnancy diagnosis was performed at d 37 ± 2 via ultrasonography. Survival rate per embryo (normal fetus with heartbeat) did not differ (P > 0.10) between methods (Exp 3, VIT = 14.1%; SLF = 16.7%; 9 of 15 pregnant cows carried twins; Exp 4, VIT = 45.7%; SLF = 38.6%; 17 of the 21 pregnant cows carried twins). Therefore, VIT was similarly efficacious to SLF for cryopreservation of bovine embryos, and simpler, requiring less equipment, time, and expense.
Keywords: bovine; direct transfer; embryo; in vitro; in vivo; vitrification